Broad-Spectrum Antiviral Activity of 3'-Deoxy-3'-Fluoroadenosine against Emerging Flaviviruses - Eyer, Luděk; Svoboda, Pavel; Balvan, Jan; Vičar, Tomáš; Raudenská, Matina; Štefánik, Michal; Haviernik, Jan; Huvarová, Ivana; Straková, Petra; Rudolf, Ivo; Hubálek, Zdeněk; Seley-Radtke, Katherine; et al. (Antimicrobial agents and chemotherapy, 2021)
Emerging flaviviruses are causative agents of severe and life-threatening diseases, against which no approved therapies are available. Among the nucleoside analogues, which represent a promising group of potentially therapeutic compounds, fluorine-substituted nucleosides are characterized by unique structural and functional properties. Despite having first been synthesized almost 5 decades ago, they still offer new therapeutic opportunities as inhibitors of essential viral or cellular enzymes active in nucleic acid replication/transcription or nucleoside/nucleotide metabolism. Here, we report evaluation of the antiflaviviral activity of 28 nucleoside analogues, each modified with a fluoro substituent at different positions of the ribose ring and/or heterocyclic nucleobase. Our antiviral screening revealed that 3'-deoxy-3'-fluoroadenosine exerted a low-micromolar antiviral effect against tick-borne encephalitis virus (TBEV), Zika virus, and West Nile virus (WNV) (EC50 values from 1.1 ± 0.1 μM to 4.7 ± 1.5 μM), which was manifested in host cell lines of neural and extraneural origin. The compound did not display any measurable cytotoxicity up to concentrations of 25 μM but had an observable cytostatic effect, resulting in suppression of cell proliferation at concentrations of >12.5 μM. Novel approaches based on quantitative phase imaging using holographic microscopy were developed for advanced characterization of antiviral and cytotoxic profiles of 3'-deoxy-3'-fluoroadenosine in vitro In addition to its antiviral activity in cell cultures, 3'-deoxy-3'-fluoroadenosine was active in vivo in mouse models of TBEV and WNV infection. Our results demonstrate that fluoro-modified nucleosides represent a group of bioactive molecules with excellent potential to serve as prospective broad-spectrum antivirals in antiviral research and drug development.
Keywords: flavivirus; mouse model; replikace viru; Deoxyadenosines; nucleoside analogue; antivirové látky; antiviral activity; infekce virem zika; Encephalitis Viruses, Tick-Borne; Prospective Studies; 3′-deoxy-3′-fluoroadenosine; Animals; Antiviral Agents; cytotoxicity; Virus Replication; deoxyadenosiny; zvířata; tick-borne encephalitis virus; myši; viry klíšťové encefalitidy; Zika Virus Infection; virus zika; Mice; Zika Virus; prospektivní studie